Investigations of a load-life with pre-stressed concrete sleepers by Ukrainian production - Rybkin, V. V.; Zayats, Y. L.; Kovalenko, V. V.; Pshinko, P. O. (Science and Transport Progress, 2011)
The analysis of operational defects of ferro-concrete sleepers and the causes of their formation is carried out.